The importance of sleep apnea index determination using 24 h ECG analysis in patients with heart rhythm disorders - Grdinić, Aleksandra; Stajić, Zoran; Grdinić, Aleksandar G.; Vučinić, Žarko; Randjelović Krstić, Violeta; Drobnjak, Dragan; Bogdanović, Predrag; Djurić, Predrag; Stevanović, Angelina; Rakonjac, Milanko; Petrović, Stanko; Gudelj, Ognjen; et al. (Vojnosanitetski pregled, 2014)
Background/Aim. A possible cause of malignant heart rhythm disorders is the syndrome of sleep apnea (periodic cessation of breathing during sleep longer than 10 seconds). Recent 24h ECG software systems have the option of determination ECG apnea index (AI) based on the change in voltage of QRS complexes. The aim of the study was to determine the significance of AI evaluation in routine 24-hour Holter ECG on a group of 12 patients. Methods. We presented a total of 12 consecutive patients with previously documented arrhythmias and the history of breathing disorders during night. They were analyzed by 24 h ECG (Medilog AR 12 plus Darwin), that is able to determine AI. Results. We presented a case series of 12 patients, 8 men and 4 women, mean age 58.75 years and the average AI 5.78. In the whole group there was a trend of increasing prevalence of complex rhythm disorders with increasing of AI and increased frequency of arrhythmias in the night phase vs day phase. Conclusion. Determination of AI using routine long term (24 h) ECG analysis is important because sleep apnea can be successfully treated as an etiological or contributing factor of arrhythmias.
Keywords: sleep apnea syndromes; arrhythmias; cardiac; electrocardiography; ambulatory